Avaliação da expressão de moléculas envolvidas em neuroinflamação e neuromodulação em Wistar Audiogenic Rats - Tulio Cezar de Souza Bernardino (2016)
Seizures and epilepsy are neurological disorders extremely frequent in clinical practice. Neuronal mechanisms that constitutes the hyperexcitability and epileptogenesis phenomenon are not totally elucidated. It´s well known the participation of the neurotransmiters in the seizures ocurrence, although, the participation of inflammatory cytokines and neurotrophic factors has been described only in the last two decades. We evaluated the effect of audiogenic seizure on the levels of IL-1, TNF, IL-6 and BDNF in Central Nervous System in Wistar Audiogenic Rats (WAR). Moreover, considering that epileptogenesis represents a neuronal plasticity environment that favors hyperexcitability, we evaluate two neuromodulatory proteins related to relevant signaling pathways, named neuronal calcium sensor-1 (NCS-1) and dopamine- and cAMP-regulated phosphoprotein of molecular weight 32 kD (DARPP-32). Levels of cytokines and BDNF were measured by ELISA. NCS-1 and DARPP-32 levels were determined by Western Blotting. After audiogenic seizure stimuli, WAR increased the expression of all studied proteins. Stimulated WAR increased expression of IL-1, TNF, IL-6 and BDNF at least in cerebral cortex compared to non-stimulated WAR. Stimulated WAR also increased expression of these cytokines and BDNF in cerebral cortex, inferior colliculus, hippocampus and striatum compared to stimulated non-audiogenic Wistar. Also, NCS-1 and DARPP-32 were increased in the hippocampus of WAR and DARPP-32 was decreased in the cerebellum of WAR compared to Wistar non-audiogenic. In conclusion, our study demonstrated that WAR neuronal hyperexcitability can be associated to neuroinflammation and neuronal plasticity mediated by BDNF, NCS-1 and DARPP-32. More research in order to concatenate the physiopathology mechanisms involved in convulsion and epilepsy related diseases are still needed. It remains unclear if WAR audiogenic seizure represents a cause or a consequence of increasing expression levels of these proteins.